THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL CLIMATE ON THE PERFORMANCE OF PRIVATE UNIVERSITIES IN INDONESIA (INTERNATIONAL SEMINAR, 2024)
Abstract: The influence of culture and organizational climate on organizational performance in private universities is the main objective of this research. The research method used in this research is Causal Explanatory research, namely research that will prove the influence of the independent variable on the dependent variable , namely the independent variables organizational culture, organizational climate. The dependent variable is the organizational performance variable of private universities. The data obtained comes from primary data sources related to research variables, and then explains the influence between variables, including the effect of moderating variables using Structural Equation Model (SEM) analysis. The results of this research show that organizational culture does not have a significant relationship with organizational performance, while organizational climate has a positive and significant relationship with organizational performance. The suggestion from this research is Organizational culture should be maintained even if it has no influence significant impact on organizational performance, because with a strong culture it will makes it easier for organizations to implement existing discipline and rules for the sake of organizational progress. A comfortable organizational climate with a supportive work environment, because this can increase organizational commitment and have an impact on organizational performance.